FORMULATION AND OPTIMIZATION OF CELECOXIB NANOEMULGEL - Bhattacharya, Sankha; Prajapati, Bhupendra G (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: The main objective of this experiment was to prepare and optimized celecoxib nanoemulgel. This formulation can be used for acuterheumatoid arthritis patients. Methods: Celecoxib is a poorly water soluble drug. We prepared celecoxib nanoemulgel to improve intrinsic solubility of celecoxib and enhancedeeper permeation throughout the skin. After several screening, the combination of acetonitrile, triacetin, campul 908P was considered for oil phase;acconon MC8-2EP as surfactant, and capmul MCM C-10 as a co-surfactant accordingly. As per Box-Behnken surface design model, optimization wasdone for all the 13 formulations. Results: Based on pseudo ternary plot, it was found that 4:1 Smix ratio was optimum and possessed maximum drug solubility. Further, screeningshown, 0.25-0.75% carbopol-940 can be a stable candidate for hydrogel preparation. Prepared nanoemulsions and hydrogels were admixed to preparenanoemulgel. Based on overlay plot, EG14* formulation was consider as optimum one, and various evaluation parameters were performed along withother formulations. Using Franz diffusion cell, in-vitro diffusion studies was performed. Almost all the formulations produces good qualitative drugrelease profile. The EG14* shown 95.50% drug release after 12th hrs with standard Higuchi plot (R2 value 0.9989). The optimum viscosity was foundto be 521Â±0.81 mPas at 100 rpm. The appearance of the formulations was milky, yellowish white with expectable pH ranged from 5.8 to 6.7. Theoptimized formulation has good spreadability coefficient, good ex-vivo diffusion enhancement factor (3.03) as compare to marketed gel. Mostly, ourformulations have less skin irritation and higher anti-inflammatory activity (92.56% of inhibition of paw edema for EG14*). Conclusion: From the thermodynamic studies, it was confirmed that EG14* maintained excellent stability profile in various heating-cooling cycle,centrifugation, and freeze-thaw cycle condition. Hence, it can be conclude that, our formulation, can be consider for pilot scale up.